Approach toward an efficient inoculum preparation stage for suspension BHK-21 cell culture - Fernández Nuñez, Eutimio Gustavo [UNESP]; Leme, Jaci; Parizotto, Letícia de Almeida; Rezende, Alexandre Gonçalves de; Costa, Bruno Labate Vale da; Boldorini, Vera Lúcia Lópes; Jorge, Soraia Attie Calil; Astray, Renato Mancini; Pereira, Carlos Augusto; Caricati, Celso Pereira; Tonso, Aldo (Springer Nature, 2014)
Mammalian cells are the most frequently used hosts for biopharmaceutical proteins manufacturing. Inoculum quality is a key element for establishing an efficient bioconversion process. The main objective in inoculation expansion process is to generate large volume of viable cells in the shortest time. The aim of this paper was to optimize the inoculum preparation stage of baby hamster kidney (BHK)-21 cells for suspension cultures in benchtop bioreactors, by means of a combination of static and agitated culture systems. Critical parameters for static (liquid column height: 5, 10, 15 mm) and agitated (working volume: 35, 50, 65 mL, inoculum volume percentage: 10, 30 % and agitation speed: 25, 60 rpm) cultures were study in T-flask and spinner flask, respectively. The optimal liquid column height was 5 mm for static culture. The maximum viable cell concentration in spinner flask cultures was reached with 50 mL working volume and the inoculum volume percentage was not significant in the range under study (10–30 %) at 25 rpm agitation. Agitation speed at 60 rpm did not change the main kinetic parameters with respect to those observed for 25 rpm. These results allowed for a schedule to produce more than 4 × 109 BHK-21 cells from 4 × 106 cells in 13 day with 1,051 mL culture medium.
Keywords: Inoculum preparation; Mammalian cells; BHK-21; Static cell culture; Suspension cell culture; Spinner flask; Bioreactor